Rancang Bangun Sistem Informasi Pelayanan Administrasi Desa Berbasis Website Menggunakan Metode Prototype di Desa Ciomas Kabupaten Ciamis - Indriani; Suhana Saputra, FAJAR (Computatio : Journal of Computer Science and Information Systems, 2023)
This research presents the design and development of a web-based village administration service information system in Ciomas Village, Ciamis Regency. The background of the study is the suboptimal village administration service that still relies on physical form filling and written communication, resulting in delays in serving the community. In this research, the prototype method was chosen as the software development approach, allowing for iteration and active user participation. The system built includes essential features such as citizen data management, online service submission, complaints, validation, verification, tracking, and document downloads. The aim of this research is to build a web-based village administration service information system using the Prototype method. The proposed system will facilitate villagers in accessing administration services online, improve the efficiency of village administration processes, and minimize the potential for human errors in data management. Black box testing and usability testing results show that the system has good learnability and memorability and has incorporated essential features in village administration services. In conclusion, this web-based village administration service information system has the potential to improve the efficiency and quality of village administration services, providing a suitable solution for the issues faced in Ciomas Village and serving as a guide for other villages adopting a similar system. Kata Kunci—Information System, Village Administration Service, Website, Prototype Method, System Testing